Zanthosimuline and Related Pyranoquinolines as Antifungal Agents for Postharvest Fruit Disease Control - Di Liberto, Melina G. (2020)
Fil: Fil: Di Liberto, Melina G. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Farmacognosia; Argentina.